COVID-19 Responses of South Korea as Hybrids of Governance Modes - Sora Lee; Ryan Wong (Frontiers Media S.A., 2021)
The countries worldwide have adapted diverse governance approaches to the pandemic to suit their contexts. While the diversity of the country-specific governance responses has been widely discussed, the hybrids nature of those governance practices has been explored less. This study analyses the responses toward COVID-19 in South Korea as responsive dialogues of different modes of governance, i.e., consensus-based hierarchy, state-sponsored market, and principle-based network. This study aims to remind us that pandemic governance needs to enable organic and responsive processes for all actors in society. This conceptual discussion of the governance modes illustrates that the pandemic allowed the emergence of the hybrids of governance modes to cope better with the complex realities of the diverse sectors and actors in South Korea. The characteristic of the responses diverges from the conventional governance classification of or market-based. It is a responsive and evolving dialogue of different modes of governance. It would be productive to think beyond the oversimplified understandings of governance modes and embrace flexible and different hybrids of governance modes to be more responsive, effective, efficient, and equitable.